2017
DOI: 10.2459/jcm.0000000000000573
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet impact on cardiovascular diseases

Abstract: : Cardiovascular disease (CVD) accounts for more than 17 million deaths per year worldwide. It has been estimated that the influence of lifestyle on CVD mortality amounts to 13.7% for smoking, 13.2% for poor diet, and 12% for inactive lifestyle. These results deeply impact both the healthy status of individuals and their skills in working. The impact of CVD on productivity loss accounts for the 24% in total costs for CVD management.Mediterranean diet (MedD) can positively impact on natural history of CVD. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 87 publications
(115 reference statements)
1
45
0
6
Order By: Relevance
“…The vegetable dietary pattern in our study had similar characteristics of high intake in the healthy/prudent dietary patterns that were most reproducible in Japanese [26][27][28] and other ethnicities [29][30][31]. Japanese and Mediterranean diets have similar features of customarily eating seafood, vegetables, and fruits, and instead of nuts that are commonly eaten in Western countries, soybean and soy products are popular among the Japanese [13,32]. A recent systematic review reported that the top three categories of the Japanese diet are soybean/soybean-derived products, seafood, and vegetables, plus rice and miso soup [33], very similar to our study.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The vegetable dietary pattern in our study had similar characteristics of high intake in the healthy/prudent dietary patterns that were most reproducible in Japanese [26][27][28] and other ethnicities [29][30][31]. Japanese and Mediterranean diets have similar features of customarily eating seafood, vegetables, and fruits, and instead of nuts that are commonly eaten in Western countries, soybean and soy products are popular among the Japanese [13,32]. A recent systematic review reported that the top three categories of the Japanese diet are soybean/soybean-derived products, seafood, and vegetables, plus rice and miso soup [33], very similar to our study.…”
Section: Discussionsupporting
confidence: 56%
“…A high intake of fruits and vegetables, salads, rice, chicken, fish, cereals, and low-fat dairy products appears to be effective in lowering blood pressure (BP) [8,9] and glycated hemoglobin levels [10]. Snacks increase the risk of hypercholesterolemia [11], while a Mediterranean diet [12,13] and Dietary Approaches to Stop Hypertension (DASH) [14] are inversely associated with metabolic syndrome (MetS). However, few studies have reported on a relationship between dietary patterns and hypertension, glucose intolerance, blood lipid profiles, and MetS in Japanese populations, which are mainly found in middle-aged and older people [10,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the HNFI, there is ample evidence that a Mediterranean Diet score is protective against CVD morbidity and mortality primarily in the general population. Studies of the Mediterranean Diet have been conducted in several settings around the world and have mostly reported significant reductions in risk of coronary heart disease , CVD progression , AMI and mortality . A recent review by Mattioli et al .…”
Section: Discussionmentioning
confidence: 99%
“…A recent review by Mattioli et al . declared that there is insufficient evidence for any clear positive effects as a result of following a Mediterranean Diet on CVD outcomes among patients with established coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found controversial data on the relationship between coffee consumption and atherosclerosis. 3,4,8 Drinking coffee was associated with acute increase in blood pressure (BP) in nonhabitual coffee drinkers; conversely, this effect was not reported in habitual coffee consumers. 9,10 However, many observational cohort studies identified no statistically significant association between daily coffee consumption at various levels and BP changes.…”
Section: Discussionmentioning
confidence: 99%